Mechanical aspects of nanoimprint patterning - CROSS, GRAHAM; O'CONNELL, BARRY SEAMUS; PETHICA, JOHN BERNARD (IEEE, 2003)
Nanoimprinting is a high resolution, parallel nanopatterning technique where, typically, a rigid stamp is brought into contact with a thin polymer film and pattern transfer achieved by the application of force and heat. The detailed mechanics of the deformation of thin film polymer layers during imprint by simple stamp geometries has not been reported. We report here measurements of various mechanical aspects of the nanoimprint process, including forces during the deformation and mechanical properties of the resultant structures. Master designs were realized in spherical blank indenters by focused ion beam milling. Deformation was measured during displacement and load controlled imprinting by a temperature controlled nanoindenter above and below the glass transition region of the polymer. The role of residual stresses in pattern transfer fidelity for isothermal stamping is shown.
PUBLISHED
Keywords: Physics